Pengaruh Pembelajaran Pendidikan Kewarganegaraan terhadap Disiplin Siswa - Duwi Putri Zulyanti; Syahril Yusuf; Ansyori Gunawan (Universitas Bengkulu, 2018)
This research is aimed to know the influence learning of civics education towards student’s discipline. This research is quantitative reserch. Method of this research that is used is Quashy Experiment, by usingTheMatching Only Pretest-Posttest Control Group Design. Instrument of the research that is used is questionnaire which is given through pretest and posttest. Data of this research result is analyzed by using descriptive analysis and inferential test which is t-test. Result of average score of posttest at experiment class is 94,25 and at controlled class is 96,51. From the result, it can conclude that there is no influence learning of civics education towards student’s discipline.